Role of Library and Information Science Professionals in the Knowledge Society - Kumar, P.K Suresh (Journal of Information, 2016)
The role of Library and Information Science (LIS) profession has been changing due to the information overload and its availability in variant forms. The 21st century has brought a lot of changes not only on the library and information services but also on the roles and expectations of the librarians and information professionals. The LIS professionals have new challenges because of unprecedented explosion of information and the application of information communication and mobile technologies in generation, dissemination and access of information. To cope with these problems, the modern library and information professionals need to change from the custodian of documents to the content managers. This paper examines (i) the importance of libraries and information centers; (ii) the transformation of libraries; (iii) temperature of the information world; (iv) the challenges faced by LIS professions (v) the new roles and skills of LIS professionals in this paradigm shift.